2000
DOI: 10.1016/s0924-9338(00)00400-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcome in first-episode psychosis treated according to an integrated model. Is immediate neuroleptisation always needed?

Abstract: In this multicentre study the two-year outcome of two groups of consecutive patients (total N = 106) with first-episode functional non-affective psychosis, both treated according to the 'need-specific Finnish model', which stresses teamwork, patient and family participation and basic psychotherapeutic attitudes, was compared. No alternative treatment facilities were available in the study sites. The two study groups differed in the use of neuroleptics: three of the sites (the experimental group) used a minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
8

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 24 publications
2
86
0
8
Order By: Relevance
“…We regard this closure of inquiry as premature. Current Scandinavian projects involving inhome family crisis intervention, avoiding use of hospitals and neuroleptics, and providing continuity of teams and approach over an extended period have shown highly promising results for the treatment of patients with newly diagnosed psychosis (Lehtinen et al, 2000;Cullberg et al, 2002). The Scandinavian results, Ciompi's Soteria replication (Ciompi et al, 1992(Ciompi et al, , 1993, and the findings reported here indicate that, contrary to popular views, minimal use of antipsychotic medications combined with specially designed psychosocial intervention for patients newly identified with schizophrenia spectrum disorders is not harmful but appears to be advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We regard this closure of inquiry as premature. Current Scandinavian projects involving inhome family crisis intervention, avoiding use of hospitals and neuroleptics, and providing continuity of teams and approach over an extended period have shown highly promising results for the treatment of patients with newly diagnosed psychosis (Lehtinen et al, 2000;Cullberg et al, 2002). The Scandinavian results, Ciompi's Soteria replication (Ciompi et al, 1992(Ciompi et al, , 1993, and the findings reported here indicate that, contrary to popular views, minimal use of antipsychotic medications combined with specially designed psychosocial intervention for patients newly identified with schizophrenia spectrum disorders is not harmful but appears to be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies reviewed by Wyatt (1991) were of a preexperimental (mirror-image) design that did not control many threats to internal validity (Carpenter, 1997). In fact, a preponderance of the few available quasiexperimental or experimentally designed early episode studies in which one group was initially not medicated (Carpenter et al, 1977;Ciompi et al, 1992Ciompi et al, , 1993Lehtinen et al, 2000;Mosher and Menn, 1978a;Rappaport et al, 1978;Schooler, 1967) show better long-term outcomes for the unmedicated subjects. In concert with the fuller presentation of Soteria results here, these studies suggest that specially designed psychosocial intervention combined with minimal medication use may be an effective treatment strategy for patients with early episode schizophrenia spectrum psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Acute Psychosis Integrated Treatment Project, which began in 1992, specifically addressed the issue of medication (Lehtinen 2000). It involved six study centres (all of which stuck to the need-adapted model), three of which employed a no or low-dose antipsychotic drug approach after an initial 3-week antipsychotic-free period (experimental group), with the remainder using antipsychotics at recommended therapeutic doses (control group).…”
Section: The Finnish Collaborative Studiesmentioning
confidence: 99%
“…In the experimental group, 43% had never taken antipsychotic medication, whereas the corresponding figure for the control group was 6%. The experimental group had received significantly less hospital treatment and had experienced fewer psychotic symptoms during the previous year (Lehtinen 2000).…”
Section: The Finnish Collaborative Studiesmentioning
confidence: 99%
“…Evidence is available from Finland that, for the majority of patients, outcome in firstepisode psychosis treated solely with expert psychosocial interventions is as good as that achieved with antipsychotics (Lehtinen et al, 2000;Seikkula et al, 2006). A psychodynamically plausible explanation for this is that teams containing expertise in the psycho logical interventions in psychosis can address the unconscious issues leading to the patient's psychotic evasive reactions and, through psychological containment, can facilitate their integration over time.…”
Section: Are Antipsychotics Always Needed?mentioning
confidence: 99%